2018
DOI: 10.1074/jbc.ra118.005365
|View full text |Cite
|
Sign up to set email alerts
|

Multiple combinations of RDL subunits diversify the repertoire of GABA receptors in the honey bee parasite Varroa destructor

Abstract: Edited by Roger J. Colbran In insects, ␥-aminobutyric acid (GABA) is the major inhibitory neurotransmitter, and GABA-gated ion channels are the target of different classes of insecticides, including fipronil. We report here the cloning of six subunits (four RDL, one LCCH3, and one GRD) that constitute the repertoire of the GABA-gated ion channel family of the Varroa mite (Varroa destructor), a honey bee ectoparasite. We also isolated a truncated GRD subunit with a premature stop codon. We found that when expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 42 publications
(69 reference statements)
9
39
0
Order By: Relevance
“…These results indicate that Phh-RDL forms a chloride permeable GABA-gated channel that does not permeate sodium ions, consistently with the pore selectivity filter sequence ( Fig. 2 ) and RDL channels from other species [51, 52]. In summary, these findings demonstrate that two novel functional homomeric receptors from the human body louse, Phh-GluCl and Phh-RDL, with respectively high affinity to glutamate or GABA were reconstituted in Xenopus oocytes.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These results indicate that Phh-RDL forms a chloride permeable GABA-gated channel that does not permeate sodium ions, consistently with the pore selectivity filter sequence ( Fig. 2 ) and RDL channels from other species [51, 52]. In summary, these findings demonstrate that two novel functional homomeric receptors from the human body louse, Phh-GluCl and Phh-RDL, with respectively high affinity to glutamate or GABA were reconstituted in Xenopus oocytes.…”
Section: Resultssupporting
confidence: 77%
“…4C-D). As previously shown in the literature, RDL and GluCls are permeable to chloride anions [35,37,[48][49][50][51]. Here, the TM2 amino acid sequences of Phh-RDL and Phh-GluCl are respectively 100% identical with RDL and GluCls from other insect species such as A. mellifera, D. melanogaster, T. castaneum (Fig.…”
Section: Xenopus Oocytessupporting
confidence: 77%
“…In addition, the arthropod phylum presents a large molecular diversity of GABA receptor subunit genes. For example, Varroa destructor , the honeybee mite, has six genes encoding GABA receptor subunits (four RDL, one GRD, and one LCCH3) (Ménard et al, 2018), while Acyrthosiphon pisum , the pea aphid, has only two genes encoding RDL subunits (Del Villar & Jones, 2018). These molecular and pharmacological diversities must lead to species‐specific physiological perturbations induced by GABA receptor‐targeting insecticides that probably act with different mechanisms and at distinct time windows.…”
Section: Discussionmentioning
confidence: 99%
“…Xenopus oocytes were prepared by collagenase (Sigma) digestion at a concentration of 1 mg·ml −1 in calcium‐free solution for 2 h at room temperature, then incubated at 19°C under gentle agitation in ND96 solution (in mM): NaCI 96, KCl 2, MgCl 2 2, CaCl 2 1.8, HEPES 5, pH 7.4 with NaOH, and supplemented with 50 mg·ml −1 gentamicin. Stage V and stage VI oocytes were injected with 20–40 nl of an aqueous solution of in vitro transcribed cRNAs of Am GABA receptor subunits, at 1 μg·μl −1 , with a stoichiometry 1:1 as previously described (Ménard et al, 2018). Macroscopic currents were recorded 1 to 3 days after injection with the two‐electrode voltage‐clamp technique, in a so‐called ND‐Herg recording solution containing (in mM) NaCl (96), KCl (3), CaCl 2 (0.5), MgCl 2 (1), and HEPES (5), with pH adjusted to 7.4 with NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…Nakao et al (2011) reported that an RDL from a fipronil-resistant strain of the small brown planthopper Laodelphax striatellus has Asn at the 2′ position. Among Acari, the VdRDL1 of the parasitic mite Varroa destructor is insensitive to fipronil and has Ser at the 2′ position and Met at the 6′ position in the M2 segment (Price and Lummis, 2014;Ménard et al, 2018). Although few reports to date have characterized the M2 segment of arthropod RDLs, the uniqueness of H305 and I309 in TuRDL needs to be examined further, particularly by comparing RDLs from acariform mites.…”
Section: Many Insect Rdls Expressed In Xenopus Oocytes Includingmentioning
confidence: 99%